Tanshinone IIA Attenuates Sevoflurane Neurotoxicity in Neonatal Mice. (April 2017) - Xia, Yimeng; Xu, Heng; Jia, Chenfei; Hu, Xiaodong; Kang, Yu; Yang, Xiaoxuan; Xue, Qingsheng; Tao, Guorong; Yu, Buwei
Abstract : BACKGROUND: Sevoflurane is the most widely used inhalational anesthetic in pediatric medicine. Despite this, sevoflurane has been reported to exert potentially neurotoxic effects on the developing brain. Clinical interventions and treatments for these effects are limited. Tanshinone IIA (Tan IIA), extracted from Salvia miltiorrhiza (Danshen), has been documented to alleviate cognitive decline in traditional applications. Therefore, we hypothesized that preadministration of Tan IIA may attenuate sevoflurane-induced neurotoxicity, suggesting that Tan IIA is a new and promising drug capable of counteracting the effects of cognitive dysfunction produced by general anesthetics. METHODS: To test this hypothesis, neonatal C57 mice (P6) were exposed to 3% sevoflurane for 2 hours with or without Tan IIA pretreatment at a dose of 10 mg/kg or 20 mg/kg for 3 consecutive days. Cognitive behavior tests such as open field tests and fear conditioning were performed to evaluate locomotor and cognitive function at P31 and P32. At P8, other separate tests, including TdT mediated dUTP Nick End Labeling (TUNEL) assay, immunohistochemistry, Western blotting, enzyme-linked immunosorbent assay, and electron microscopy, were performed. The mean differences among groups were compared using 1-way analysis of variance followed by Bonferroni post hoc multiple comparison tests. RESULTS: Repeated exposure to sevoflurane leads to significant cognitive impairment in mice, which may be explained by increased apoptosis, overexpression of neuroinflammatory markers, and changes in synaptic ultrastructure. Interestingly, preadministration of Tan IIA ameliorated these neurocognitive deficits, as shown by increased freezing percentages on the fear conditioning test (sevoflurane+Tan IIA [20 mg/kg] versus sevoflurane, mean difference, 19, 99% confidence interval for difference, 6.4–31, P < .0001, n = 6). The treatment also reduced the percentage of TUNEL-positive nuclei (sevoflurane versus sevoflurane+Tan IIA [20 mg/kg], 2.6, 0.73–4.5, P = .0004, n = 6) and the normalized expression of cleaved caspase-3 (sevoflurane versus sevoflurane+Tan IIA [20 mg/kg], 0.27, 0.02–0.51, P = .0046, n = 5). Moreover, it attenuated the production of the neuroinflammatory mediators interleukin (IL)-1β and IL-6 (normalized sevoflurane versus sevoflurane+Tan IIA [20 mg/kg]: IL-1β: 0.75, 0.47–1.0; P < .0001; IL-6: 0.66, 0.35–0.97; P < .0001; n = 10 per group). Finally, based on measurements of postsynaptic density, the treatment preserved synaptic ultrastructure (sevoflurane+Tan IIA [20 mg/kg] versus sevoflurane, 42, 20–66; P < .0001; n = 12 per group). CONCLUSIONS: These results indicate that Tan IIA can alleviate sevoflurane-induced neurobehavioral abnormalities and may decrease neuroapoptosis and neuroinflammation.